Hydrogen trapping at dislocations, carbides, copper precipitates and grain boundaries in a dual precipitating low-carbon martensitic steel. (December 2022) - McCarroll, Ingrid E.; Lin, Yu-Chen; Rosenthal, Alexander; Yen, Hung-Wei; Cairney, Julie M.
Abstract: By using atom probe tomography to detect deuterium in a dual precipitating low carbon martensitic steel we provide insight into the relationship between hydrogen (H), carbon, and microstructural features. TiC and Cu precipitates were found to provide H trapping sites, however, dislocations without C were not observed to trap H. The order of trapping from highest to lowest concentrations of deuterium (D) is as follows: TiC decorated dislocations > high energy grain boundaries > low energy grain boundaries. Graphical abtract: Image, graphical abstract